Early Prenatal MRI of Cervical “Abortive” Myelocystocele: Case Report and Review of the Literature - Talenti, Giacomo; Giussani, Carlo; Parazzini, Cecilia; Izzo, Giana; Canonico, Francesco; Vergani, Patrizia; Righini, Andrea (Neuropediatrics, 2017)
Cervical abortive myelocistocele is a very rare congenital malformation. In this case report, we describe the prenatal magnetic resonance imaging (MRI) of such entity in a 20-week gestational age fetus, whose imaging features showed to be different from the only other previous prenatal report. We underscored the value of fetal MR for counseling and prognosis, especially when assessing the integrity of the spinal cord.
Keywords: fetal MR; spinal dysraphism; myelocystocele